Laminated Film

A laminated film with distinct particle sizes and binder resins in its coating layers addresses the challenge of achieving both water and oil repellency and adhesion, outperforming existing materials in terms of repellency and structural integrity.

JP7618985B2Active Publication Date: 2025-01-22TOYOBO CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2020150042
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2020-09-07
Publication Date
2025-01-22
Estimated Expiration
2040-09-07

AI Technical Summary

Technical Problem

Existing films lack sufficient water and oil repellency while maintaining adhesion to a resin base material, and there is a need for improved antifouling properties.

Method used

A laminated film structure is developed with two coating layers, one containing smaller hydrophobic fine particles on the surface and larger particles beneath, using specific particle size differences and binder resins to enhance adhesion and repellency.

Benefits of technology

The film achieves high water and oil repellency with excellent adhesion to the resin base, surpassing the performance of conventional materials like polytetrafluoroethylene, and maintains transparency and structural integrity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007618985000001
    Figure 0007618985000001
  • Figure 0007618985000002
    Figure 0007618985000002
Patent Text Reader

Abstract

To provide a film excellent in liquid repellency (water-repellent and oil-repellent property) while maintaining adhesion to a resin base material.SOLUTION: There is provided a laminated film in which a coating layer positioned on at least a resin base material film side directly or through other layer on a resin base material film, and a coating layer positioned on the surface side are laminated in this order, in which a primary particle average diameter of fine particles contained in a coating layer positioned on the surface side is smaller than a primary particle average diameter of the fine particles contained in the coating layer positioned on the resin base material film side by 200 nm or more, and at least one fine particles of the fine particles contained in the coating layer positioned on the resin base material film side and the fine particles contained in the coating layer positioned on the surface side are fine particles whose surface is made hydrophobic.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a laminated film, and more particularly to a coated laminated film having water- and oil-repellent properties. [Background technology]

[0002] Materials that exhibit water- and oil-repellent properties on their surfaces are industrially important in fields where antifouling is required. To achieve antifouling, it is necessary to reduce the interaction between contaminants and the material surface, which is usually achieved by making the material surface water- and oil-repellent.

[0003] In Patent Document 1, a film with high antireflection and antiglare properties is obtained by distributing reactive inorganic fine particles that crosslink with a binder component ubiquitously in the surface region of the interface opposite to the substrate. However, there is no particular description of the water and oil repellency of the film.

[0004] In Patent Document 2, the internal cavities of the hollow microparticles ensure a low refractive index and enable anti-reflection, but the water contact angle is only about 100 degrees, which is not sufficient for liquid repellency. Patent Document 3 proposes a film that uses hydrophobic microparticles and particles with different particle sizes to obtain stable non-adhesive properties. However, there is no description of the adhesion between the non-adhesive layer and the base layer. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] JP 2009-42628 A [Patent Document 2] JP 2004-258267 A [Patent Document 3] JP 2017-100785 A Summary of the Invention

[0006] The present invention has been made against the background of the problems of the conventional technology. That is, an object of the present invention is to provide a film having excellent liquid repellency (water and oil repellency) while maintaining adhesion to a resin substrate. [Means for solving the problem]

[0007] As a result of extensive research into achieving the above object, the present inventors have found that the above problems can be solved by the following means, and have arrived at the present invention. That is, the present invention has the following configuration. 1. A laminated film in which at least a coating layer located on the resin substrate film side and a coating layer located on the surface side are laminated in that order, either directly or via another layer, on a resin substrate film, and the average primary particle diameter of the fine particles contained in the coating layer located on the surface side is smaller by 200 nm or more than the average primary particle diameter of the fine particles contained in the coating layer located on the resin substrate film side, and at least one of the fine particles contained in the coating layer located on the resin substrate film side and the fine particles contained in the coating layer located on the surface side is fine particles whose surface has been hydrophobized. 2. The laminate film according to item 1 above, wherein the resin substrate film is a polyethylene terephthalate film or a polyethylene naphthalate film. 3. The laminate film described in the above 1 or 2, wherein the average primary particle diameter of the fine particles contained in the coating layer located on the surface side is 20 nm to 500 nm, and the average primary particle diameter of the fine particles contained in the coating layer located on the resin substrate film side is 1 μm or more and 15 μm or less. 4. A laminate film described in any one of claims 1 to 3, wherein the binder resin contained in the coating layer located on the resin substrate film side and / or the binder resin contained in the coating layer located on the surface side is an acid-modified polyolefin resin and / or a polyester resin. Effect of the Invention

[0008] The film of the present invention uses two types of particles with different particle sizes, and localizes relatively small particles with a hydrophobic surface in the surface coating layer and relatively large particles in the coating layer located between the resin substrate film and the surface coating layer, thereby exhibiting high liquid repellency and good adhesion between the coating layer and the resin substrate film. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0009] The present invention provides a laminated film having excellent water and oil repellency and excellent adhesion between a coating layer and a resin substrate film.

[0010] (Base film) The laminated film in the present invention has a resin substrate film. The material of this resin substrate film is not particularly limited, but examples of the resin constituting the resin substrate film include polyolefins such as polyethylene, polypropylene, polystyrene, and diene polymers, polyesters such as polyethylene terephthalate, polypropylene terephthalate, polybutylene terephthalate, and polyethylene naphthalate, polyamides such as nylon 6, nylon 6,6, nylon 6,10, and nylon 12, acrylate resins such as polymethyl methacrylate, polymethacrylic acid esters, polymethyl acrylate, and polyacrylic acid esters, polyacrylic acid resins, and polymethacrylic acid esters. Examples of the resin substrate include cellulose-based resins such as cellulose acetate and ethyl cellulose, polyarylates, aramids, polycarbonates, polyphenylene sulfides, polyphenylene oxides, polysulfones, polyethersulfones, polyetheretherketones, polyetherimides, polyimides, polyamideimides, aromatic hydrocarbon-based polymers such as polybenzimidazole, polybenzoxazole, and polybenzothiazole, fluorine-based resins such as polytetrafluoroethylene and polyvinylidene fluoride, epoxy resins, phenolic resins, novolac resins, and benzoxazine resins. Among these, from the viewpoint of transparency and dimensional stability, resin substrate films made of polyester resins and acrylate resins are preferred. Specific examples of polyester resins include polyethylene terephthalate, polypropylene terephthalate, polybutylene terephthalate, and polyethylene naphthalate. Among these, from the viewpoint of physical properties, polyethylene terephthalate, polyethylene naphthalate, and polyimides are preferred, and from the viewpoint of balance between physical properties and cost, polyethylene terephthalate is particularly preferred.

[0011] The resin substrate film may be a single layer, or may have two or more layers laminated thereon. When two or more layers are laminated, the same or different films may be laminated. A resin composition may also be laminated on the resin substrate film. Furthermore, various additives may be contained in the substrate film as necessary within the range in which the effects of the present invention are achieved. Examples of additives include antioxidants, light resistance agents, gelation inhibitors, organic wetting agents, antistatic agents, ultraviolet absorbers, and surfactants. When the resin substrate film is composed of two or more layers, additives may also be contained according to the function of each layer. In order to improve the handling properties, such as the slipperiness and windability, of the resin substrate film, inactive particles may be contained in the substrate film.

[0012] In the present invention, the thickness of the resin substrate film is not particularly limited, but is preferably 5 μm to 300 μm. More preferably, it is 10 μm to 280 μm, and even more preferably, it is 12 μm to 260 μm. If it is 5 μm or more, it is easy to apply the coating layer when laminating it, and if it is 300 μm or less, it is advantageous in terms of cost.

[0013] The surface of the resin substrate film may be untreated, but it may also be subjected to a surface treatment such as plasma treatment, corona treatment or flame treatment, or may be provided with a primer coating layer to improve adhesion.

[0014] (fine particles)

[0015] The coating layer of the laminated film in the present invention contains fine particles. The type of fine particles is not particularly limited. For example, at least one type of fine particles such as silica (silicon dioxide), alumina, titania, zirconia, etc. can be used. These may be synthesized via any compound, and known or commercially available particles may be used. In particular, silica (silicon dioxide) particles are preferred because they can be easily hydrophobized as described below.

[0016] The fine particles may have a hydrophobic surface, and the method of hydrophobization is not particularly limited. For example, hydrophilic oxide particles may be hydrophobized by surface treatment. That is, hydrophilic oxide particles may be surface-treated with any reagent such as a silane coupling agent, and the surface may be hydrophobized.

[0017] As a method for hydrophobizing fine particles, such as silica particles, surface treatment using various known reagents, such as silicone oil, silane coupling agents, and silazane, is preferably used. In particular, from the viewpoint of exhibiting excellent water and oil repellency, it is more preferable to introduce fluorine-based functional groups, such as 1H,1H,2H,2H-perfluorooctyl group, 1H,1H,2H,2H-perfluorodecyl group, 1H,1H,2H,2H-perfluorohexyl group, and 3,3,3-trifluoropropyl group, alkyl groups, such as methyl group, ethyl group, n-propyl group, isopropyl group, n-butyl group, isobutyl group, sec-butyl group, tert-butyl group, and octyl group, alkenyl group, alkynyl group, vinyl group, cyclohexyl group, styryl group, phenyl group, and trimethylsilyl group, to the surface. Among these, hydrophobic oxide particles into which trimethylsilyl groups have been introduced are preferred, and hydrophobic silica into which trimethylsilyl groups have been introduced is particularly preferred, since they exhibit superior water and oil repellency.

[0018] In the present invention, at least a coating layer located on the resin substrate film side and a coating layer located on the surface side are laminated in this order directly or via another layer (e.g., a primer easy-adhesion layer, etc.) on the resin substrate film, and the primary particle average diameter of the fine particles contained in the coating layer located on the surface side is 450 nm or more smaller than the primary particle average diameter of the fine particles contained in the coating layer located on the resin substrate film side, and it is preferable from the viewpoint of water and oil repellency of the outermost surface of the coating layer that at least one of the fine particles contained in the coating layer located on the resin substrate film side and the fine particles contained in the coating layer located on the surface side is a fine particle having a hydrophobic surface. If either one of the fine particles contained in the coating layer located on the resin substrate film side and the fine particles contained in the coating layer located on the surface side is a fine particle having a hydrophobic surface, a preferable water and oil repellency of the coating layer outer surface can be obtained. Of course, it is a particularly preferable embodiment that the surface of both the fine particles having a relatively large particle diameter contained in the coating layer located on the resin substrate film side and the fine particles having a relatively small particle diameter contained in the coating layer located on the surface side are fine particles having a hydrophobic surface.

[0019] In the present invention, the measurement results by an X-ray photoelectron spectroscopy (ESCA) can be used as an index of the modification rate of the functional groups having water- and oil-repellency on the surface of the hydrophobized fine particles. Specifically, the atomic composition ratio can be obtained in a depth region of about 10 nm, and the ratio of specific atoms constituting the functional groups having water- and oil-repellency, for example, carbon atoms, can be compared. In the present invention, from the viewpoint of exhibiting excellent water- and oil-repellency, for example, in the case of hydrophobic silica into which trimethylsilyl groups have been introduced, the ratio of carbon atoms is preferably 8 at% or more.

[0020] In the present invention, at least two types of fine particles having different particle diameters are used as described above. In the present invention, the size of the average primary particle diameter can be determined as a result of morphological observation by a microscope such as a scanning electron microscope or a transmission electron microscope. Specifically, the average diameter of 20 particles randomly selected in these microscope observations is taken as the average primary particle diameter. The average primary particle diameter of particles with an irregular shape can be calculated as the circle equivalent diameter. The circle equivalent diameter is the value obtained by dividing the area of ​​the observed particles by π, calculating the square root, and multiplying it by two.

[0021] In the present invention, the average primary particle diameter of the relatively small particles contained in the coating layer located on the surface side is preferably 20 nm to 500 nm, more preferably 40 nm to 400 nm, and even more preferably 50 nm to 300 nm. By satisfying the above range, it is possible to achieve both water repellency and oil repellency, and sufficient liquid repellency can be obtained.

[0022] The average primary particle diameter of the relatively large particles contained in the coating layer located on the resin substrate film side in the present invention is preferably 1 μm to 15 μm, more preferably 1.2 μm to 12 μm, and even more preferably 1.5 μm to 10 μm. If it is 1 μm or more, sufficient unevenness can be formed and liquid repellency can be improved, and if it is 15 μm or less, transparency can be obtained, which is preferable.

[0023] In the present invention, the difference in particle size between the relatively large particles contained in the coating layer located on the resin substrate film side and the relatively small particles contained in the coating layer located on the surface side is preferably 200 nm or more, more preferably 600 nm or more, and even more preferably 1.5 μm or more. By satisfying the above range, unevenness with different densities can be appropriately formed on the outermost surface of the coating layer, and a highly liquid-repellent surface can be obtained, which is preferable. On the other hand, if the difference in particle size between the two is 14 μm or less, transparency can be obtained, which is preferable.

[0024] (binder resin) In the present invention, each coating layer preferably contains a binder resin. The binder resin is not particularly limited as long as it is a component that can be well bonded to the resin substrate film. For example, it is preferable to use a polyester resin, an acid-modified polyolefin resin, a polyurethane resin, an epoxy resin, an acrylic resin, etc. Furthermore, from the viewpoint of adhesion to the resin substrate, it is preferable to use a polyester resin or an acid-modified polyolefin resin for layers other than the outermost layer, and from the viewpoint of preventing a decrease in water and oil repellency, it is particularly preferable to use a polyester resin, an acid-modified polyolefin resin, or an acrylic silicone resin for the outermost layer. It is a particularly preferable embodiment that the binder resin contained in the coating layer located on the resin substrate film side and / or the binder resin contained in the coating layer located on the surface side is an acid-modified polyolefin resin and / or a polyester resin.

[0025] The acid-modified polyolefin resin is preferably at least partially polyolefin or unsaturated carboxylic acid-modified polyolefin, more preferably unsaturated carboxylic acid-modified polypropylene or unsaturated carboxylic acid-modified polyethylene, and most preferably unsaturated carboxylic acid-modified polypropylene.

[0026] As the unsaturated carboxylic acid, maleic acid, fumaric acid, acrylic acid, methacrylic acid, and their anhydrides are preferable, and maleic anhydride and maleic acid are most preferable, as they can form a coating layer having high adhesion to the resin substrate.

[0027] The acid value of the acid-modified olefin resin is preferably 2 mgKOH / g to 35 mgKOH / g, more preferably 5 mgKOH / g to 35 mgKOH / g, and even more preferably 5 mgKOH / g to 25 mgKOH / g. If the acid value is higher than the lower limit, the adhesion to the resin or the resin substrate is good, and if the acid value is lower than the upper limit, the water- and oil-repellency of the resin itself is utilized in the liquid repellency of the coating layer, which is preferable.

[0028] The binder resin may be used after mixing with a curing agent to crosslink the resin, and the curing agent used is preferably isocyanate, epoxy, melamine, or carboxylic acid, and more preferably epoxy or melamine. This makes it possible to form a coating layer containing silica particles while maintaining the transparency of the resin substrate.

[0029] (Ingredients in the coating layer) The coating layer in the present invention may contain components other than the above-mentioned fine particles and binder resin.Specific examples of the components include antioxidants, curing agents, light resistance agents, gelling inhibitors, organic wetting agents, antistatic agents, ultraviolet absorbers, surfactants, etc., and these components can be appropriately contained as necessary.

[0030] The solid content of the coating liquid is preferably 0.5% by mass to 20% by mass, more preferably 1% by mass to 15% by mass, and even more preferably 3% by mass to 10% by mass. Within the above range, the unevenness of the fine particles is easily exposed on the coating surface, and the coating property is also good, which is preferable.

[0031] The mixing ratio of the binder resin and the relatively large particle diameter fine particles (binder resin:large particle diameter fine particles) contained in the coating layer located on the resin substrate film side is preferably in the range of 40:60 to 10:90, more preferably 50:50 to 20:80, and further preferably 50:50 to 30:70. Within the above range, the fine particles are unlikely to fall off from the binder while the unevenness of the fine particles is expressed on the outermost surface of the coating layer, which is preferable.

[0032] The mixing ratio of the binder resin and the relatively small particle diameter fine particles contained in the coating layer located on the surface side (binder resin:small particle diameter fine particles) is preferably in the range of 50:50 to 5:95, more preferably 33:67 to 5:95, and further preferably 25:75 to 5:95. Within the above range, the water and oil repellency of the small particle diameter fine particles is expressed on the outermost surface of the coating layer, but the fine particles are unlikely to fall off from the binder, which is preferable.

[0033] (Coating layer thickness) In the present invention, it is also a preferred embodiment to further laminate a coating layer (hereinafter sometimes referred to as a first coating layer) containing the binder resin as described above and not containing fine particles between the coating layer located on the resin substrate film side and the resin substrate film, and the adhesion between the entire coating layer and the resin substrate film is further improved. It is a particularly preferred embodiment that the binder resin of the first coating layer is an acid-modified polyolefin resin or a polyester resin. The film thickness after drying of the first coating layer is preferably 100 nm or more and 2 μm or less, more preferably 300 nm or more and 1 μm or less. By satisfying this range, the adhesion between other layers to be laminated and the PET film is improved, and the thin film allows curing in a short time. Of course, the first coating layer may not be required. The film thickness after drying of the coating layer (hereinafter sometimes referred to as a second coating layer) located on the resin substrate film side is also affected by the particle diameter of the relatively large particle diameter fine particles used, but is preferably 2 μm or more and 10 μm or less. By satisfying this range, a preferable uneven state that contributes to the water- and oil-repellency of the outermost surface of the coating layer is formed, and the adhesion when a first coating layer is present can be maintained by interaction with the binder. The film thickness after drying of the coating layer located on the surface side (hereinafter sometimes referred to as the liquid-repellent layer) is preferably 300 nm or more and 2 μm or less, and more preferably 300 nm or more and 1 μm or less. By satisfying this range, the adhesion of the entire coating layer to the resin substrate film can be maintained, and the water- and oil-repellency of the fine particles with a relatively small particle size is also prominently expressed, which is preferable.

[0034] (solvent) The solvent used in coating is not particularly limited, and for example, organic solvents such as water, alcohols, ketones, normal hexane, cyclohexane, toluene, butyl acetate, glycols, etc. are preferred, organic solvents such as toluene, cyclohexane, hexane, etc. are more preferred, and toluene is the most preferred. These solvents can provide high solubility for the binder resin, making it possible to prepare a uniform coating liquid.

[0035] (average primary particle diameter of fine particles) It can be determined as a result of morphological observation using a microscope, such as a scanning electron microscope or a transmission electron microscope. Specifically, the average diameter of 20 particles randomly selected in these microscope observations is taken as the primary particle average diameter.

[0036] (Method of measuring acid value) The acid value (mgKOH / g-resin) in the present invention refers to the amount of KOH required to neutralize 1g of acid-modified polyolefin, and was measured in accordance with the test method of JIS K0070 (1992). Specifically, 1g of acid-modified polyolefin was dissolved in 100g of xylene adjusted to 100°C, and then titrated with 0.1mol / L potassium hydroxide ethanol solution [product name "0.1mol / L ethanolic potassium hydroxide solution", manufactured by Wako Pure Chemical Industries, Ltd.] at the same temperature using phenolphthalein as an indicator. At this time, the amount of potassium hydroxide required for titration was converted to mg to calculate the acid value (mgKOH / g).

[0037] (Water and oil repellency) The water and oil repellency of the laminated film according to the present invention can be evaluated by a known method. Specifically, the water repellency can be evaluated by contact angle measurement using water, and the oil repellency can be evaluated by contact angle measurement using diiodomethane. The preferred range of the contact angle with water in the present invention is 110 degrees or more, more preferably 120 degrees or more. The larger the contact angle with water, the better, and there is no particular upper limit, but in reality, the upper limit is about 170 degrees. A contact angle with water of 110 degrees or more is preferable because it shows excellent water repellency, and a contact angle of 120 degrees or more is more preferable because it shows water repellency equal to or higher than that of conventional fluorine-based resin sheets represented by polytetrafluoroethylene (PTFE). The preferred range of the contact angle with diiodomethane in the present invention is 60 degrees or more, more preferably 90 degrees or more. The larger the contact angle with diiodomethane, the better, and there is no particular upper limit, but in reality, the upper limit is about 160 degrees. A contact angle of 60 degrees or more with diiodomethane is preferable from the viewpoint of imparting oil repellency that can suppress oil stains, etc., and a contact angle of 90 degrees or more is even more preferable since it exhibits oil repellency equal to or greater than that of conventional fluorine-based resin sheets.

[0038] (Laminated film manufacturing process) In the production of the laminated film of the present invention, the coating method is not particularly limited. For example, it can be produced according to known methods such as roll coating, gravure coating, bar coating, doctor blade coating, spin coating, spray coating, and brush coating. In the present invention, it is preferable that a layer containing fine particles and a layer not containing fine particles are laminated as necessary, so that particles of different particle sizes are ubiquitous at the top and bottom of the laminated film. During coating, it is preferable that a layer containing fine particles with a relatively large particle size is coated first, and then a layer containing fine particles with a relatively small particle size is laminated, so that small particle diameter fine particles are present on the outermost surface of the coating layer. The solvent used when coating by these methods is not particularly limited, and for example, organic solvents such as water, alcohols, ketones, normal hexane, cyclohexane, toluene, butyl acetate, and glycols can be appropriately selected and used. These solvents may be used alone or in combination. The amount of hydrophobic oxide particles dispersed in the solvent can be selected at any ratio that allows a uniform dispersion to be obtained. The method of drying after coating may be either natural drying or heat drying, but heat drying is more preferable from the viewpoint of industrial production. The drying temperature is not particularly limited as long as it does not affect the components contained in the substrate film or coating layer, but is usually preferably 150°C or less, and more preferably 50°C or more and 140°C or less. The drying method is not particularly limited, and a known method for drying a film, such as a hot plate or a hot air oven, can be used. The drying time is appropriately selected depending on other conditions such as the drying temperature, but may be within a range that does not affect the components contained in the substrate film or coating layer. The coating process may be a so-called offline coating method performed in a separate process after the formation of the resin substrate film, or a so-called in-line coating method in which a coating liquid is applied to an unstretched sheet or a uniaxially stretched film during the production process of the resin substrate film and stretched in at least one axial direction. EXAMPLES

[0039] The present invention will be further described below with reference to specific examples, but the present invention is not limited to these examples. First, the evaluation methods employed in the present invention will be described.

[0040] (Contact angle measurement) The contact angle of the coating layer surface of the laminated film produced was measured with respect to the solvent. A contact angle meter CA-X manufactured by Kyowa Interface Science Co., Ltd. was used to measure the contact angle. Pure water and diiodomethane were used as the measurement solvents. The contact angle of water (hereinafter sometimes abbreviated as WCA) was measured after 10 seconds from a 1.8 μL water droplet being dropped. The contact angle of diiodomethane (hereinafter sometimes abbreviated as DCA) was measured after 10 seconds from a 0.9 μL diiodomethane droplet being dropped.

[0041] (Measurement of the average diameter of primary particles) The average primary particle diameter of hydrophobic oxide particles was determined as a result of observations using a scanning electron microscope, a transmission electron microscope, and a confocal laser microscope. Specifically, the average diameter of 20 particles randomly selected in these microscope observations was taken as the average primary particle diameter. The average primary particle diameter of irregular particles can be calculated as the equivalent circle diameter. The equivalent circle diameter is calculated by dividing the area of ​​the observed particles by π, calculating the square root, and multiplying it by two.

[0042] (ESCA measurement of microparticles with hydrophobic surfaces) The dispersion of the hydrophobic particles was dropped onto a clean aluminum foil and dried to form a thin film of hydrophobic particles on the aluminum foil. The aluminum foil was quickly dried to prevent surface contamination as much as possible, and immediately sampled for surface composition analysis. The device is K-Alpha + (manufactured by Thermo Fisher Scientific) was used. Details of the measurement conditions are shown below. During the analysis, background removal was performed by the Shirley method. The surface composition ratio was the average value of the measurement results of three or more locations on the resin substrate film where Al was not detected. Measurement conditions Excitation X-ray: Monochrome AlKα line X-ray output: 12kV, 6mA Photoelectron escape angle: 90 degrees Spot size: 400μmΦ Pass energy: 50eV Step: 0.1eV

[0043] (Adhesion) The adhesion between the film and the coating layer was judged by a visual test using cellophane tape: a 24 mm wide piece of cellophane tape was applied to the coating surface, pressed firmly with a finger, and then peeled off vigorously to visually check whether the coating layer had peeled off. 〇: No peeling ×: Peeling

[0044] The following are reagents used in the studies described in the Examples. Vylon (registered trademark) RV280 (Toyobo polyester resin) YD128 (Epoxy resin made by Nippon Steel Chemical & Materials) TETRAD(registered trademark)-X (multifunctional epoxy resin manufactured by Mitsubishi Gas Chemical) MS-001 (Methylated melamine resin made by Sanwa Chemical) · Silica® 310P (Fuji Silysia Chemical Co., Ltd., hydrophilic colloidal silica with a primary particle average diameter of 2.7 μm) · Silica® 470 (Fuji Silysia Chemical Co., Ltd., hydrophilic colloidal silica with a primary particle average diameter of 14.1 μm)

[0045] <Production Example of Acid-Modified Polyolefin A> In a 1L autoclave, 100 parts by mass of polypropylene (Tm: 80°C, weight average molecular weight 135,000), 150 parts by mass of toluene, 8.5 parts by mass of maleic anhydride, and 4 parts by mass of di-tert-butyl peroxide were added, and the mixture was heated to 140°C and further stirred for 1 hour. After the reaction was completed, the reaction liquid was poured into a large amount of methyl ethyl ketone to precipitate a resin. This resin was further washed several times with methyl ethyl ketone to remove unreacted maleic anhydride. The obtained resin was dried under reduced pressure to obtain maleic anhydride-modified polyolefin A (acid value 12.6 mgKOH / g, weight average molecular weight 60,000, Tm 80°C), which is an acid-modified polyolefin.

[0046] <Production Example of Acid-Modified Polyolefin Solution A-1> 10 parts by mass of the acid-modified polyolefin A was weighed out into a reaction vessel, and 90 parts by mass of toluene was added thereto and stirred for 1 hour or more to obtain an acid-modified polyolefin solution A-1 having a solid content concentration of 10% by mass.

[0047] <Production Example of Acid-Modified Polyolefin Solution A-2> 23 parts by mass of acid-modified polyolefin solution A-1, 27 parts by mass of toluene, 0.2 parts by mass of YD128 as a crosslinking agent, and 0.02 parts by mass of TETRAD-X as a crosslinking catalyst were added to a sample bottle, and the mixture was stirred at room temperature for 5 minutes to obtain acid-modified polyolefin solution A-2 with a solids concentration of 5% by mass.

[0048] <Production Example of Polyester Solution B-1> 20 parts by mass of RV280 (polyester resin manufactured by Toyobo), 90 parts by mass of toluene, and 90 parts by mass of methyl ethyl ketone were added to a sample bottle and stirred at room temperature for 1 hour to prepare polyester solution B-1 (solids concentration 10% by mass).

[0049] <Production Example of Polyester Solution B-2> Polyester solution B-2 (solids concentration 5% by mass) was prepared by adding 23 parts by mass of polyester solution B-1, 27 parts by mass of toluene, 0.2 parts by mass of melamine resin MS-001 as a crosslinking agent, and 0.02 parts by mass of paratoluenesulfonic acid (PTS) as a crosslinking catalyst to a sample bottle and stirring at room temperature for 5 minutes.

[0050] <Method of synthesizing small silica particle dispersion C-1> 100 parts by mass of tetraethoxysilane and 439 parts by mass of ethanol were mixed in a reaction vessel 1. 179 parts by mass of ethanol, 13 parts by mass of ammonia water (25%), and 26 parts by mass of deionized water were mixed in a reaction vessel 2, and then the contents of the reaction vessel 2 were transferred dropwise to the reaction vessel 1. At this time, the dropwise addition took 10 minutes to prevent a rapid reaction. After the dropwise addition, the reaction solution was left at 20°C for 48 hours. Then, ammonia and water were distilled off to prepare a silica particle dispersion (average primary particle average diameter 45 nm). Then, 150 parts by mass of hexamethyldisilazane was added and heated at 65°C for 2 days to prepare a silica particle dispersion C-1 modified with a trimethylsilyl group. In order to confirm the solid content concentration of the silica particle dispersion, 5 grams of the silica particle dispersion was measured out in an aluminum cup (1.3 grams) and heated in an oven at 150°C for 24 hours or more to remove the residual solvent ethanol and water. The aluminum cup after removal was weighed to be 1.55 grams, so the solid content in 5 grams of silica microparticle dispersion was calculated to be 0.25 grams, and the solid content concentration of the silica microparticle dispersion was confirmed to be 5 mass%. When preparing the coating liquid, the ethanol in the silica microparticle dispersion was removed and the same amount of toluene was added as the removed ethanol, and the coating liquid was prepared as a toluene dispersion. The result of ESCA analysis of the silica microparticles surface-modified with trimethylsilyl groups was that C (carbon atoms) was 14.0 at%.

[0051] <Method of synthesizing small silica particle dispersion C-2> 100 parts by mass of tetraethoxysilane and 226 parts by mass of ethanol were mixed in a reaction vessel 1. 178 parts by mass of ethanol, 13 parts by mass of ammonia water (25%), and 240 parts by mass of deionized water were mixed in a reaction vessel 2, and then the contents of the reaction vessel 2 were transferred dropwise to the reaction vessel 1. At this time, the dropwise addition took 30 minutes to prevent a rapid reaction. After the dropwise addition, the reaction solution was left at 20°C for 48 hours. Then, ammonia and water were distilled off to prepare a silica particle dispersion (average primary particle average diameter 450 nm). Then, 150 parts by mass of hexamethyldisilazane was added and heated at 65°C for 2 days to prepare silica particle dispersion C-2 modified with trimethylsilyl groups. In order to confirm the solid content concentration of the silica particle dispersion, 5 grams of the silica particle dispersion was measured out in an aluminum cup (1.3 grams) and heated in an oven at 150°C for 24 hours or more to remove the residual solvent ethanol and water. The aluminum cup after removal was weighed to be 1.55 grams, so the solid content in 5 grams of silica microparticle dispersion was calculated to be 0.25 grams, and the solid content concentration of the silica microparticle dispersion was confirmed to be 5 mass%. When preparing the coating liquid, the ethanol in the silica microparticle dispersion was removed and the same amount of toluene was added as the removed ethanol, and the coating liquid was prepared as a toluene dispersion. The result of ESCA analysis of the silica microparticles surface-modified with trimethylsilyl groups was that C (carbon atoms) was 12.1 at%. <Method of synthesizing small silica particle dispersion C-3> 100 parts by mass of tetraethoxysilane and 439 parts by mass of ethanol were mixed in a reaction vessel 1. 179 parts by mass of ethanol, 13 parts by mass of aqueous ammonia (25%), and 26 parts by mass of deionized water were mixed in a reaction vessel 2, and then the contents of the reaction vessel 2 were transferred dropwise to the reaction vessel 1. At this time, the dropwise addition took 10 minutes to prevent a rapid reaction. After the dropwise addition, the reaction solution was left at 20°C for 48 hours. Then, ammonia and water were distilled off to prepare a silica particle dispersion (average primary particle average diameter 45 nm). In order to confirm the solid content concentration of the silica microparticle dispersion, 5 grams of the silica microparticle dispersion was weighed out in an aluminum cup (1.3 grams) and heated in an oven at 150°C for 24 hours or more to remove the residual solvent ethanol and water. The aluminum cup after removal was weighed to be 1.55 grams, so the solid content in 5 grams of the silica microparticle dispersion could be calculated to be 0.25 grams, and the solid content concentration of the silica microparticle dispersion was confirmed to be 5% by mass. After that, when preparing the coating liquid, the ethanol in the silica microparticle dispersion was removed and the same amount of toluene as the removed ethanol was added to prepare a toluene dispersion of silica microparticles C-3. The result of ESCA analysis of the silica microparticles surface-modified with trimethylsilyl groups was that C (carbon atom) was 5.4 at%. <Method of synthesizing small silica particle dispersion C-4> 100 parts by mass of tetraethoxysilane and 390 parts by mass of ethanol were mixed in a reaction vessel 1. 179 parts by mass of ethanol, 13 parts by mass of ammonia water (25%), and 76 parts by mass of deionized water were mixed in a reaction vessel 2, and then the contents of the reaction vessel 2 were transferred dropwise to the reaction vessel 1. At this time, the dropwise addition took 10 minutes to prevent a rapid reaction. After the dropwise addition, the reaction solution was left at 20°C for 48 hours. Then, ammonia and water were distilled off to prepare a silica particle dispersion (average primary particle average diameter 150 nm). Then, 150 parts by mass of hexamethyldisilazane was added, and the mixture was heated at 65°C for 2 days to prepare silica particle dispersion C-4 modified with trimethylsilyl groups. In order to confirm the solid content concentration of the silica particle dispersion, 5 grams of the silica particle dispersion was measured out in an aluminum cup (1.3 grams) and heated in an oven at 150°C for 24 hours or more to remove the residual solvent ethanol and water. The aluminum cup after removal was weighed to be 1.55 grams, so the solid content in 5 grams of silica microparticle dispersion was calculated to be 0.25 grams, and the solid content concentration of the silica microparticle dispersion was confirmed to be 5 mass%. When preparing the coating liquid, the ethanol in the silica microparticle dispersion was removed and the same amount of toluene as the removed ethanol was added, and the coating liquid was prepared as a toluene dispersion. The result of ESCA analysis of the silica microparticles surface-modified with trimethylsilyl groups was that C (carbon atoms) was 10.2 at%.

[0052] <Method for preparing large silica particle dispersion D-1> To 10 parts by mass of Cylysia 310P, 190 parts by mass of ethanol was added, stirred for 30 minutes, and then ultrasonically irradiated for 30 minutes to prepare a 5% ethanol dispersion of Cylysia 310P. Then, 40 parts by mass of hexamethyldisilazane was added, and the mixture was heated at 65°C for 2 days. Then, the hexamethyldisilazane remaining without modifying the ethanol or silica particles was distilled off by distillation, and ethanol was added until the total mass of the initial Cylysia 310P and ethanol was the same, thereby preparing a large-sized silica microparticle dispersion modified with trimethylsilyl groups (solid content concentration 5% by mass). Then, in order to prepare a coating liquid, the ethanol in the silica microparticle dispersion was removed, and the same amount of toluene as the removed ethanol was added to prepare a large-sized silica microparticle dispersion D-1 dispersed in toluene. The result of ESCA analysis of the silica microparticles surface-modified with trimethylsilyl groups was C (carbon atom) 9.0 at%.

[0053] <Preparation method of large silica particle dispersion D-2> Large-particle silica microparticle dispersion D-2 (solid content concentration 5 mass%) was prepared in toluene in the same manner as in the preparation of D-1, except that the silica particles used were changed to Silica 470. The result of ESCA analysis of the silica microparticles surface-modified with trimethylsilyl groups was that C (carbon atoms) was 9.2 at%.

[0054] <Preparation method of large silica particle dispersion D-3> To 10 parts by mass of Cylysia 310P, 190 parts by mass of toluene was added, stirred for 30 minutes, and then ultrasonically irradiated for 30 minutes to prepare a toluene dispersion with a concentration of Cylysia 310P of 5% by mass. The surface analysis result of the silica fine particles by ESCA showed that C (carbon atom) was 5.2 at%.

[0055] <Production example of coating solution E-1> Coating solution E-1 (solid concentration 5% by mass) was prepared by adding and mixing 40 parts by mass of acid-modified polyolefin solution A-1 (solid concentration 10% by mass), 80 parts by mass of large particle silica microparticle dispersion D-1 (solid concentration 5% by mass), 44 parts by mass of toluene, 0.2 parts by mass of epoxy curing agent YD128 (solid concentration 100% by mass), and 0.02 parts by mass of catalyst TETRAD (registered trademark)-X (solid concentration 100% by mass) to a sample bottle. Similarly, coating solutions E-2 to E-4 were prepared under conditions in which the binder and the microparticles used were changed. Details of the coating solutions are shown in Table 1.

[0056] <Production example of coating solution F-1> In a sample bottle, 20 parts by mass of acid-modified polyolefin solution A-1 (solid concentration 10% by mass), 400 parts by mass of small particle silica microparticle dispersion C-1 (solid concentration 5% by mass), 24 parts by mass of toluene, 0.2 parts by mass of epoxy curing agent YD128 (solid concentration 100% by mass), and 0.02 parts by mass of catalyst TETRAD (registered trademark)-X (solid concentration 100% by mass) were added and mixed to prepare coating liquid F-1 (solid concentration 5% by mass). Similarly, coating liquids F-2 to F-4 were prepared under conditions in which the binder and the microparticles used were changed. Details of the coating liquids are shown in Table 1.

[0057] [Table 1]

[0058] <Preparation of laminated film> Example 1 Polyester solution B-2 was applied to the corona-treated surface of Toyobo Ester (registered trademark) film (product number: E5100, thickness: 75 μm), which is a film made of polyethylene terephthalate (hereinafter, sometimes referred to as PET film), by bar coating using bar coater #5, and then dried at 120 ° C for 10 minutes to produce a first coating layer (film thickness after drying: about 570 nm). Thereafter, coating solution E-1 prepared by the method described in the above coating solution production example was applied with an applicator with a gap of 5 mil, and then dried at 80 ° C for 5 minutes to produce a second coating layer (film thickness after drying of the second coating layer: about 6.5 μm), and coating solution F-1 was applied with bar coater #5 and dried at 110 ° C for 60 minutes to produce a liquid-repellent layer, thereby obtaining a laminated film (film thickness after drying of the liquid-repellent layer: about 570 nm).

[0059] (Examples 2 to 8) The coating liquids for the second coating layer and the water-repellent layer were changed according to Table 2 below to obtain laminate films of Examples 2 to 8.

[0060] Example 9 A laminated film was obtained in the same manner as in Example 1, except that the liquid-repellent layer was applied by spray coating using an airbrush.

[0061] Example 10 A laminated film was obtained in exactly the same manner as in Example 9, except that the coating liquid used for coating the liquid-repellent layer was changed to F-2.

[0062] Example 11 A laminated film was obtained in exactly the same manner as in Example 1, except that the coating liquid used for coating the liquid-repellent layer was changed to F-3.

[0063] Example 12 A laminated film was obtained in exactly the same manner as in Example 1, except that the coating liquid used for coating the liquid-repellent layer was changed to F-4.

[0064] Example 13 A laminated film was obtained in exactly the same manner as in Example 1, except that the resin substrate used was changed to a Teonex (registered trademark) film (product number: Q51, thickness 38 μm), which is a polyethylene naphthalate film.

[0065] Example 14 A laminated film was obtained in exactly the same manner as in Example 1, except that the coating liquid used for the second coating layer was changed to E-5.

[0066] Example 15 Except for changing the coating liquid used for the liquid-repellent layer to F-5, a laminate film was obtained in exactly the same manner as in Example 1. The contact angle, adhesion evaluation results with the resin substrate film, and particle size measurement results by microscopic observation for Examples 1 to 15 are shown in Table 2.

[0067] Comparative Example 1 Polyester solution B-2 (solid content 5% by mass) was applied to the corona-treated surface of PET film E5100 using bar coater #5, and then dried at 110° C. for 60 minutes to obtain a laminated film.

[0068] Comparative Example 2 A laminated film of Comparative Example 2 was obtained in the same manner as in Example 1, except that no liquid-repellent layer was formed.

[0069] Comparative Example 3 A laminated film of Comparative Example 3 was obtained in the same manner as in Example 3, except that no liquid-repellent layer was formed.

[0070] Comparative Example 4 A laminated film of Comparative Example 4 was obtained in the same manner as in Example 1, except that the second coating layer was not formed.

[0071] Comparative Example 5 A laminated film of Comparative Example 5 was obtained in the same manner as in Example 2, except that the second coating layer was not formed.

[0072] Comparative Example 6 Polyester solution B-2 was applied to the corona-treated surface of Toyobo Ester (registered trademark) film (product number: E5100, thickness: 75 μm) made of polyethylene terephthalate (hereinafter, sometimes referred to as PET film) by bar coating using bar coater #5, and then dried at 120°C for 10 minutes to produce a first coating layer (film thickness after drying: approximately 570 nm). Thereafter, coating solution F-6 was applied with an applicator with a gap of 0.5 mil, and then dried at 80°C for 5 minutes to produce a second coating layer (film thickness after drying: approximately 6.5 μm for the second coating layer), and then coating solution F-1 was applied with bar coater #5 and dried at 110°C for 60 minutes to produce a liquid-repellent layer, thereby obtaining a laminated film (film thickness after drying: approximately 570 nm for the liquid-repellent layer). The contact angle, adhesion evaluation results with resin substrate film, and particle size measurement results by microscopic observation for Comparative Examples 1 to 6 are shown in Table 2.

[0073] [Table 2] [Industrial Applicability]

[0074] The present invention provides a laminated film having excellent water and oil repellency and antifouling properties. The laminated film of the present invention is useful because it can be expected to be used in applications such as packaging, covering, and release substrates.

Claims

1. at least a coating layer located on the resin substrate film side and a coating layer located on the surface side are laminated in this order on a resin substrate film directly or via another layer, the average primary particle diameter of fine particles contained in the coating layer located on the surface side is smaller by 200 nm or more than the average primary particle diameter of fine particles contained in the coating layer located on the resin substrate film side, and at least one of the fine particles contained in the coating layer located on the resin substrate film side and the fine particles contained in the coating layer located on the surface side is fine particles having a hydrophobic surface, the fine particles contained in the coating layer located on the surface side are hydrophobic silica having a trimethylsilyl group introduced therein; The ratio of carbon atoms of the hydrophobic silica measured by X-ray photoelectron spectroscopy (ESCA) is 12.1 at% or more; The binder resin contained in the coating layer located on the surface side is an acid-modified polyolefin resin and / or a polyester resin. Laminated film.

2. 2. The laminate film according to claim 1, wherein the resin substrate film is a polyethylene terephthalate film or a polyethylene naphthalate film.

3. The laminate film according to claim 1 or 2, wherein the average primary particle diameter of the fine particles contained in the coating layer located on the surface side is 20 nm to 500 nm, and the average primary particle diameter of the fine particles contained in the coating layer located on the resin substrate film side is 1 μm or more and 15 μm or less.

4. 4. The laminate film according to claim 1, wherein the binder resin contained in the coating layer located on the resin substrate film side is an acid-modified polyolefin resin and / or a polyester resin.

Citation Information

Patent Citations

  • Antireflection film, method for manufacturing antireflection film, and antireflection member

    JP2004258267A

  • Anti-glare film

    JP2009042628A

  • Lid material

    JP2014046984A

  • Heat adhesive film having non-adhesiveness of liquid

    JP2017100785A

  • Manufacturing method of resin container

    JP2020104869A